Simultaneous determination of arabinitol and mannose by gas-liquid chromatography in experimental candidiasis. - de Repentigny, L (1983)
A method is described for the simultaneous quantitation of D-arabinitol and D-mannose in serum by gas-liquid chromatography as an aid for the diagnosis of disseminated candidiasis. Both variables were observed as per-O-acetylated aldononitrile derivatives in each chromatographic run of sera from immunosuppressed rabbits experimentally infected with Candida albicans 3181A.